MENINGKATKAN PERILAKU DISIPLIN MELALUI PEMBIASAAN PADA ANAK KELOMPOK B DI TK MUSLIMAT NU 10 RANDUAGUNG SINGOSARI - Siti Nur Azizah; Muhammad Hanif; Yorita Febry Lismanda (Jurnal Dewantara, 2020)
Habituation is an activity carried out continuously and in the daily life of the child so that is becomes a good habit. This habituation includes aspects of moral development and religious values, the development of socio emotional and independence. Habit is very important to do early on so that it will have a big impact on the personality of children when the are older. Because habituation that has been done since childhood will be firmly remembered. Planting disciplinary behavior in early childhood in TK Muslimat NU 10 is carried out through the daily learning process,planting disciplinary behavior will be continuos.